2023
DOI: 10.1038/s41467-022-35512-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Euro 2020 championship on the spread of COVID-19

Abstract: Large-scale events like the UEFA Euro 2020 football (soccer) championship offer a unique opportunity to quantify the impact of gatherings on the spread of COVID-19, as the number and dates of matches played by participating countries resembles a randomized study. Using Bayesian modeling and the gender imbalance in COVID-19 data, we attribute 840,000 (95% CI: [0.39M, 1.26M]) COVID-19 cases across 12 countries to the championship. The impact depends non-linearly on the initial incidence, the reproduction number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…An increase in the number of COVID-19 cases and hospitalisations starts towards the end of the group stages, peaking at the beginning of the quarter final stage of the tournament. Such an increase may support [ 19 ], who found that there was little effect on COVID-19 transmission associated with a nation hosting a UEFA 2020 match, but speculated that hosting an entire tournament such as FIFA 2022 could increase COVID-19 transmission. The increase in cases and hospitalisations is then followed by a decline, most probably reflecting less interest from certain fan-bases as their national side drops out of the tournament.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An increase in the number of COVID-19 cases and hospitalisations starts towards the end of the group stages, peaking at the beginning of the quarter final stage of the tournament. Such an increase may support [ 19 ], who found that there was little effect on COVID-19 transmission associated with a nation hosting a UEFA 2020 match, but speculated that hosting an entire tournament such as FIFA 2022 could increase COVID-19 transmission. The increase in cases and hospitalisations is then followed by a decline, most probably reflecting less interest from certain fan-bases as their national side drops out of the tournament.…”
Section: Discussionmentioning
confidence: 90%
“…The 2022 FIFA World Cup hosted in Qatar was the first multi-continental sporting MGE of the post COVID-19 era to allow foreign spectators [15][16][17]. Denhing et al (2023) and Subedi et al (2022) [18,19] highlighted the potential for disease spread at the world cup. Therefore, we chose to use the 2022 FIFA World Cup as a test case of the framework we developed.…”
Section: Introductionmentioning
confidence: 99%
“…Our Bayesian model simulates the spread of each variant separately using a discrete renewal process 50 53 . In our model, COVID-19 spreads with an inferred time-dependent effective reproduction number 54 , where the contribution of each variant to is modulated by a time-invariant factor .…”
Section: Methods Overviewmentioning
confidence: 99%
“…(2023) and Subedi et al . (2022) (18; 19) highlighted the potential for disease spread at the world cup. Therefore, we chose to use the 2022 FIFA World Cup as a test case of the framework we developed, assessing various strategies to mitigate COVID-19 spread through match attendee testing and visitor vaccination requirements.…”
Section: Introductionmentioning
confidence: 99%